Профилометр для контроля микрогеометрии коллекторов электрических машин - Упадышев Д. М. Дмитрий Петрович; Боровиков Ю. С. Юрий Сергеевич; Васильев А. С. Алексей Сергеевич; Саблуков В. Ю. Виталий Юрьевич
опубл. 27.06.11